2018
DOI: 10.1080/14686996.2018.1550625
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of high-voltage cathodes for advanced lithium-ion batteries – differential capacity study on differently balanced cells

Abstract: The degradation of LiNi 0.5 Mn 1.5 O 4 (LNMO) cathodes were investigated using different cell designs (half cells, full cells cathode-limited, anode-limited and cathode-limited with pre-charge). Half cells based on Li/LNMO show long-cycle stability due to the unlimited source of electrochemically available lithium. Full-cell configurations with Li 4 Ti 5 O 12 /LNMO are limited in their cycling performance and durability. Differential capacity studies during continuous cycling reveal a systematic intensity chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…By comparing the observed degradation rate of the half-cells (this study) and full cells and considering the spectroscopic observation of electrolyte degradation products, the detection of Ni and Mn on the anode side (Supporting Information), and the fact that adding fresh electrolyte will temporally recover the cell (Supporting Information), one can conclude that there is (i) a decomposition of the cathode active material (LNMO) itself, leading to a deliberation of Ni and Mn, and (ii) oxidative/reductive decomposition of the liquid electrolyte by self-discharge, leading to a formation of Li-containing degradation products. The lithium ions in the degradation products are no longer available for charge transport (electrochemical availability).…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the observed degradation rate of the half-cells (this study) and full cells and considering the spectroscopic observation of electrolyte degradation products, the detection of Ni and Mn on the anode side (Supporting Information), and the fact that adding fresh electrolyte will temporally recover the cell (Supporting Information), one can conclude that there is (i) a decomposition of the cathode active material (LNMO) itself, leading to a deliberation of Ni and Mn, and (ii) oxidative/reductive decomposition of the liquid electrolyte by self-discharge, leading to a formation of Li-containing degradation products. The lithium ions in the degradation products are no longer available for charge transport (electrochemical availability).…”
Section: Resultsmentioning
confidence: 99%
“…LiNi 1/3 Mn 1/3 Co 1/3 O 2 (NMC), as the most common representative, has already been studied extensively [3,4], including work aimed at improving the materials' properties by employing strategies such as doping and coating [5][6][7]. Among other cathode materials such as LiNi 0.5 Mn 1.5 O 4 (LNMO) spinels [8], NMC has already found its way into commercialization within the automotive sector, with Nissan being a prominent adopter of this material from the start.…”
Section: Introductionmentioning
confidence: 99%
“…Differential capacities as a function of voltage were analyzed for full pouch cells at 0.2C cycling rate between 2.5 and 4.2 V. Figure 5 shows that the differential capacity curves can be used for battery ageing evaluation, given that separate anode and cathode values are obtained with the use of REs, enabling analysis of distinct potential curve features. [32][33][34][35][36] Here it can be observed that the intensity for both the cathode and anode decreases with increase in cycling from the 2nd to 70th cycles. The main feature of the overall cell, cathode, and anode with respect to RE monitoring is the loss of the dQ/dV initial peak 1, which shrinks its initial peak by %40-50%, and the inflexion point between peak 1 and 2 by %10%.…”
Section: Electrochemical Measurements and Stability Monitoringmentioning
confidence: 82%